Ageist attitudes block young adults' ability for compassion toward incapacitated older adults. (20th February 2015) - Bergman, Yoav S.; Bodner, Ehud
ABSTRACT: Background: Upon encountering older adults, individuals display varying degrees of prosocial attitudes and behaviors. While some display compassion and empathy, others draw away and wish to maintain their distance from them. The current study examined if and how ageist attitudes influence the association between the sight of physical incapacity in older age and compassionate reactions toward them. We predicted that ageist attitudes would interfere with the ability to respond to them with compassion. Methods: Young adults ( N = 149, ages 19–29) were randomly distributed into two experimental conditions, each viewing a short video portraying different aspects of older adult physicality; one group viewed older adults displaying incapacitated behavior, and the other viewed fit behavior. Participants subsequently filled out scales assessing aging anxieties, and ageist and compassionate attitudes. Results: Ageism was associated with reduced compassion toward the figures. Moreover, viewing incapacitated older adults led to increased concern toward them and perceived efficacy in helping them. However, significant interactions proved that higher scores of ageism in response to the videos led to increased need for distance and reduced efficacy toward incapacitated adults, an effect not observed among subjects with lower ageism scores. Conclusions: Ageism seems to be a factor which disengages individuals from older adults displaying fragility, leading them to disregard social norms which dictate compassion. The results are discussed from the framework of terror management theory, as increased mortality salience and death-related thoughts could have led to the activation of negative attitudes which, in turn, reduce compassion.